Multi-purpose droop controllers incorporating a passivity-based stabilizer for unified control of electronically interfaced distributed generators including primary source dynamics. (July 2016) - Azimi, Seyed Mohammad; Afsharnia, Saeed
Abstract: This paper presents multi-purpose droop controllers for electronically-interfaced distributed generators (EI-DGs). These controllers allow the micro-grids to operate in grid-connected mode, islanded mode and mode transition transients with a unique control configuration. The active and reactive-power sharing among EI-DGs are satisfied by the proposed droop controllers in islanded mode. On the other hand, in the grid-connected mode, the droop controllers adjust the output active and reactive-powers of EI-DGs at the pre-programmed constant levels. The provision of sufficient damping capability and maintenance of the transient stability in all operational modes of EI-DGs are warranted by the suggested stabilizer. This stabilizer, which is designed using the passivity-based control (PBC) approach, is incorporated in the droop controllers to dampen power-angle, frequency and voltage deviations during large transients using solely local information. The primary source dynamics of EI-DGs are also considered. It is analytically proven that the presence of the primary source dynamics leads to attenuation of the damping capability of EI-DGs in transients. To compensate the adverse effect of the primary source dynamics during transients a novel compensator is inserted in the frequency-droop loop. Finally, time-domain simulations are performed on a multi-resources MG to verify the analytical results compared to those obtained, based on a recently-developed strategy. Highlights: A novel voltage droop structure has been developed which enhances voltage control in micro-grids. Developing a decentralized stabilizer designed using the passivity-based-control (PBC) in micro-grids. The impacts of the primary source dynamics during transients were considered analytically and an effective compensator was proposed. The effects of the voltage and frequency droop gains were analyzed using analytically approach in transients.